2000
DOI: 10.1364/ao.39.005415
|View full text |Cite
|
Sign up to set email alerts
|

From the grating scale monitor to the generalized seeing monitor

Abstract: An instrument named the grating scale monitor for measuring the outer scale L0 from the angle-of-arrival (AA) fluctuations of a perturbed wave front was developed a few years ago at Nice University. The AA is detected with a 5-ms time resolution by modulation of the stellar image in a small telescope with a grating. One uses the normalized covariance of AA fluctuations to estimate L0. A new version of this instrument, the generalized seeing monitor (GSM) is described. It consists of four identical modules for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 21 publications
8
135
0
1
Order By: Relevance
“…During its previous missions it was found that L 0 follows a log-normal distribution with a dispersion of log(L 0 ) of about 0.23, and, rather similar median values, ranging from 24 to 31 m, were obtained in all GSM campaigns (Ziad et al 1999). Large isolated values of L 0 , called "bursts", were also noted at all sites.…”
Section: Outer Scale Statisticssupporting
confidence: 57%
See 1 more Smart Citation
“…During its previous missions it was found that L 0 follows a log-normal distribution with a dispersion of log(L 0 ) of about 0.23, and, rather similar median values, ranging from 24 to 31 m, were obtained in all GSM campaigns (Ziad et al 1999). Large isolated values of L 0 , called "bursts", were also noted at all sites.…”
Section: Outer Scale Statisticssupporting
confidence: 57%
“…The actual instrument is described in Martin et al (1998b) and Tokovinin et al (1998b). Description and performance analysis are also given in Ziad et al (1999). We refer the interested readers to the reports on the previous GSM missions Tokovinin et al 1998a).…”
Section: Principle Of the Gsmmentioning
confidence: 99%
“…It contains three DIMM (Differential Image Motion Monitor) telescopes (Aristidi et al 2005a), one of them on top of a 5 m high platform, and the other two at the snow surface level, being operated together in the GSM (Grating Scale Monitor) mode (Ziad et al 2000). Scintillation and isoplanatic angle measurements are also carried out.…”
Section: Introductionmentioning
confidence: 99%
“…For λ = 0.5 μm, D 10 cm and h 10 km, W(h) resembles the h 5/3 dependence. Then θ 0 can be derived from the scintillation index as (Ziad et al 2000)…”
Section: Isoplanatic Anglementioning
confidence: 99%